2015
DOI: 10.3109/10253890.2015.1064891
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events and incident metabolic syndrome: the Hoorn study

Abstract: Stressful life events are associated with the metabolic syndrome in cross-sectional studies, but prospective studies addressing this issue are rare and limited. We therefore evaluated whether the number of stressful life events is associated with incident metabolic syndrome. We assessed the association between the number of stressful life events experienced in the 5 years up until baseline and incident metabolic syndrome after 6.5 years at follow-up in the Hoorn study, a middle-aged and elderly population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…This finding is consistent with those reported by Meyer et al 35 that reported prejudice-related acute stress was associated with more general stressful life events and that racial/ethnic and sexual minority groups reported higher levels than their less socially disadvantaged counterparts. In addition to being linked with chronic medical conditions, [26][27][28] stressful life events have also been linked with increases in weight, BMI and waist circumference. 36,37 Our analyses revealed that after adjusting for stressful life events (in addition to BMI, sociodemographic variables and physical activity), perceived weight discrimination was no longer significantly associated with significantly elevated prevalence risk of high cholesterol and incidence of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with those reported by Meyer et al 35 that reported prejudice-related acute stress was associated with more general stressful life events and that racial/ethnic and sexual minority groups reported higher levels than their less socially disadvantaged counterparts. In addition to being linked with chronic medical conditions, [26][27][28] stressful life events have also been linked with increases in weight, BMI and waist circumference. 36,37 Our analyses revealed that after adjusting for stressful life events (in addition to BMI, sociodemographic variables and physical activity), perceived weight discrimination was no longer significantly associated with significantly elevated prevalence risk of high cholesterol and incidence of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Using the data from the National Survey of Alcohol and Related Conditions (NESARC), the current study examined whether perceived discrimination increased risk of reporting new diagnosis of chronic medical conditions. Given that stressful life events may also increase risk for cardiovascular conditions, metabolic conditions and arthritis, we additionally examined whether perceived weight discrimination confers an additional or unique contribution to observed associations with medical conditions. In addition to the analyses with a total sample, we completed gender‐stratified analyses to explore whether the patterns of associations between perceived weight discrimination and chronic medical conditions differed by gender.…”
Section: Introductionmentioning
confidence: 99%
“…the response to experience-based changes in cognitive, emotional and/or behavioral phenotypes [39]. Psychological stress has furthermore been associated with the development of metabolic syndrome and its components in prospective studies [19, 40]. The role of bariatric surgery in resetting biological alterations associated with long-term stress exposure is however not clear, and the potential mechanisms for weight regain after bariatric surgery remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…perceived stress. Thus, the results of cross-sectional or prospective studies on the association of stress with T2D have been variable [8690]. However, a 35-year study of perceived stress in Swedish men reported a significant association with later diabetes, and a similar result was observed in persons with burn-out syndrome [91, 92].…”
Section: Overview Of Environmental and Lifestyle Factors Increasing Tmentioning
confidence: 99%